Peran Ekonomi Syariah dalam Mendorong Implementasi Green Economy di Indonesia - Fiesca Maini Asri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine the role of Islamic economics in promoting the implementation of green economy in Indonesia. Using a library research method with a qualitative approach, this study analyzes various literatures, policy documents, and official reports related to Islamic economics and environmental sustainability. The findings indicate that Islamic economics plays a significant role through three main pathways: (1) theological foundations consisting of principles such as khalifah (stewardship), amanah (trusteeship), mizan (balance), and maqasid al-shariah which provide an ethical basis for environmentally friendly activities; (2) Islamic financial instruments such as green financing from Islamic banking, green sukuk, and the allocation of ZISWAF (zakat, infaq, sadaqah, and waqf) funds for environmental programs; and (3) supporting policies such as the OJK Regulation on Sustainable Finance, the Master Plan of Islamic Economy, and regional regulations in various provinces. However, its implementation still faces challenges including low literacy levels, the absence of a uniform green shariah certification standard, limited economic incentives, and a consumptive culture among the public. This study recommends strengthening regulations and standardization, enhancing human resource capacity, developing green products and incentives, as well as fostering multi-stakeholder collaboration to realize a sustainable green shariah economy in Indonesia